Integrated Multitrophic Aquaculture By-Products with Added Value: The Polychaete Sabella spallanzanii and the Seaweed Chaetomorpha linum as Potential Dietary Ingredients - Stabili, Loredana (Mar Drugs, 2019)
Aquaculture expansion is limited by the negative environmental impact of the waste and the need for alternative sources in the diet of reared fish. In this framework, for the first time, the survival rates, biomass gain, and fatty acid profiles of the polychaete Sabella spallanzanii and the macroalga Chaetomorpha linum, reared/cultivated as bioremediators in an integrated multitrophic aquaculture system (IMTA), were evaluated for their potential reuse applications. Results showed that these organisms represent a natural source of omega-3 and omega-6. On account of the overall results and the high biomass obtained as by-products, a preliminary study was performed employing both S. spallanzanii and C. linum as new dietary ingredients to feed different sized Dicentrarchus labrax. Fish survival rate, biomass growth, and specific growth rate were determined resulting in no significant differences between control and treated fishes. Histological analyses showed no alterations of the stomach tunica mucosa and submucosa in treated fishes. The eco-friendly approaches applied in the here-realized IMTA system could guarantee the achievement of sustainable by-products represented by the bioremediators S. spallanzanii and C. linum, as well as their reliability as a natural source of compounds beneficial to fish and human health.